Cognitive orientation to daily occupational performance (CO-OP) approach as telehealth for a child with developmental coordination disorder: a case report - Shiozu, Hiroyasu; Kurasawa, Shigeki (Frontiers in Rehabilitation Sciences, 2023)
Aim: This study aimed to propose a possible interventional form of occupational therapy through a case study report of the applied Cognitive Orientation to daily Occupational Performance (CO-OP) approach as telehealth for a child with developmental coordination disorder (DCD). Methods: The intervention method was CO-OP-based tele-occupational therapy for a boy with DCD and his mother; 10 sessions were conducted using a video-conferencing system. This study used the Canadian Occupational Performance Measure (COPM) and the Performance Quality Rating Scale (PQRS) as assessment tools. The PQRS evaluated each occupational performance based on videos recorded during the online sessions and videos taken by the mother of the child. Results: The CO-OP approach improved COPM performance and satisfaction as well as PQRS scores in the following five goals: (1) handwriting, (2) column addition, (3) jumping rope, (4) playing on the bar, and (5) riding a bicycle. Conclusions: An online approach based on the CO-OP was realistic and effective, to some extent. Continuing to develop telehealth interventions in the future is recommended.